Relationship of the nanocrystal morphology and atomistic structure with respect to the superstructure ordering within PbS- and Gold-Mesocrystals. Issue 1705 (14th July 2014) - Bahrig, Lydia; Haubold, Danny; Röder, Falk; Hickey, Stephen G.; Eychmüller, Alexander
ABSTRACT: The relationship between nanoparticle geometry and their two dimensional assembly is investigated in order to provide insights into the three dimensional arrangement of mesocrystals. The crystal structure of the nanoparticles and their homogeneity are investigated during structure formation on the mesoscale whereby effects such as fibrillation have been observed.